Complete chloroplast genome sequence of the three-flowered maple, Acer triflorum (Sapindaceae). Issue 2 (2nd April 2020) - Xia, Xinhe; Yu, Xuedan; Fu, Qidi; Zheng, Yongqi; Zhang, Chuanhong
Abstract: Acer triflorum (Sapindaceae: Acer ) is a deciduous arbor species with excellent ornamental values because of its reddish-tan exfoliating bark and attractive three leaflets. However, due to some wild populations being threatened by poor seed viability, it was listed as vulunerable in China. Its complete chloroplast (cp) genome was obtained using genome Illumina pair-end sequencing data. The cp genome was 156, 024 bp in length with a typical circular structure, containing a large single copy (LSC) region of 85, 815 bp and a small single copy (SSC) region of 18, 051 bp, which were separated by a pair of inverted repeats (IRs) (26, 079 bp). A total of 136 genes were annotated, including 88 protein-coding genes, 40 tRNAs and 8 rRNAs. The overall GC content was 37.9%. The phylogenetic analysis suggested that A. triflorum was the most closely related to A. griseum. The complete chloroplast genome of A. triflorum is useful for assessment of genetic diversity and further for taxonomic study of Acer L.